Acute toxicity assessment of newly nanoformulated gallic acid-loaded graphene oxide using zebrafish embryonic model - Abdul Ghafor, Ahmad Ashraful Hadi (2022)
Gallic acid (GA) is a phenolic compound found in almost all plants and has been reported to possess powerful health benefits such as anti-oxidant, anti-inflammatory, anti-cancer, and anti-diabetic properties. However, GA suffers a short half-life when administered in vivo. Recent studies have employed graphene oxide (GO), a biocompatible and cost-effective graphene derivative, as a nanocarrier for GA. This newly formulated nano-compound is called gallic acid-loaded graphene oxide (GAGO). However, the toxicity effect of this formulated nano-compound has not been fully studied. Thus, the present study aims to evaluate the toxicity and oxidative stress effects of GAGO nanoformulation, using the zebrafish embryonic model. GAGO was exposed to zebrafish embryos (n ≥ 30; 24 hours post-fertilization (hpf)) at five different concentrations ranged between 0-500 μg/mL for up to 96 hours of exposure. Pure GO, pure GA and distilled water were used as controls to GAGO. The development of embryos was monitored twice daily throughout the study. Significant high mortality rate, delayed hatching rate, low heartbeat, and high reactive oxygen species (ROS) content were recorded in GO-treated embryos exposed to concentrations ≥ 50 μg/mL, at all-time points (p < 0.05). GA also exhibits similar effects in concentration- and timedependent manners. Interestingly, when compared to GO and GA, significant improvement in the survival rate was observed in GAGO-treated embryos at all concentrations tested and all time points measured. Furthermore, GAGO also exhibits normal ROS level when compared to GA and GO. Noticeable malformations of pericardial and yolk sac edema were observed in embryos treated with GAGO. Altogether, the present data demonstrates that GAGO nanofomulation demonstrates significant improved toxicity profile compared to its pure compounds, GO and GA (p < 0.05). Further study is still warranted to correlate the toxicity of GAGO with its effective concentrations at molecular level, in in vitro and in vivo models.